Men ; your Goodyear dealer's magazine. - Goodyear Tyre & Rubber Co. (Aust.) (Sydney : Goodyear Tyre & Rubber Co.)
Aboriginal tooth rite: Describes the rite of tooth pulling during a ceremony that was performed in front of a photographer at Millingimbi Mission station; Boomerangs at Lords: Describes the historical cricket matches played at Lords Cricket Ground in England in 1868 by an Australian Aboriginal cricket team; notes that at the end of each match some of the Aboriginal team demonstrated the correct throwing of boomerangs and spears; lists the names of the Aboriginal players in the match.
title from cover.
Description based on Vol. 3, no. 1.
Keywords: History; Sport - Cricket; Initiation - Tooth avulsion; England; Milingimbi (Central Arnhem Land NT SD53-02); Australia